The First Experience of Using the Developed Modified Allogenic Bone Grafts in the Surgical Treatment of Patients With Severe Fractures of the Surgical Neck of the Humerus - A. Y. Vaza; A. M. Fain; N. V. Borovkova; I. E. Galankina; M. S. Makarov; O. A. Zabavskaya; R. S. Titov; L. N. Ziminа; G. A. Nefedova; V. B. Bondarev; A. S. Mironov; I. N. Ponomarev (Неотложная медицинская помощь)
BACKGROUND Fractures of the proximal humerus are more common in older adults. Two options for surgical treatment of the same fractures are routinely performed — primary arthroplasty and osteosynthesis with metal fixators. Both methods are most effective in elderly patients for augmentation of the proximal humerus. For this purpose, methyl methacrylate cement or bone allo-/autografts are used. However, the incidence of unsatisfactory functional results after surgery remains high.AIM OF STUDY To develop allogeneic graft to strengthen the proximal humerus in the osteosynthesis of a comminuted fracture with a lack of bone tissue which has osteoconductive properties and capable of being a carrier of biologically active substances.MATERIAl AND METHODS The head, neck and portion of diaphysis of a fibula of a cadaver were used for a graft. The graft 6–8 cm long was formed and saturated with a collagen solution. Ten patients with 4-fragment fractures of the proximal humerus underwent surgery. X-rays and computed tomography of the operated joint were performed the day after surgery, and then, 6 weeks, 6 months, and one year after the surgery. The follow-up period ranged from 6 to 18 months.RESUlTS When evaluating osteoconductive effect in cell culture during saturation with collagen, the content cells on the surface of bone was 5–8 thousand/cm2 and 16–18 thousand/cm2 on the sample, saturated with plasma and growth factors. The studied bone grafts were biocompatible and non-toxic for fibroblast culture. On the surface of the bone graft without collagen adhesion of minimum number of cells occurred. After saturation of the graft with collagen, the adhesive activity of cells on the bone matrix increased, which indicated the presence of an osteoconductive effect. The addition of plasma saturated with growth factors promoted an increase in the number of adhered cells; therefore, the graft can be used as a carrier of biologically active substances. Postoperative X-ray didn’t reveal secondary varus displacement of the head in any patient (except for ununiformed fracture case).CONClUSION The developed graft is non-toxic, does not possess immunogenicity, has more pronounced osteoconductive properties in comparison with native bone allografts, which contributes to its colonization with cells. The use of such a graft in clinical practice makes it possible to achieve healing of the fracture and prevent secondary displacement of fragments.